Are all wines made from various grape varieties beneficial in the prevention of myocardial infarction and stroke? - Masahiro Iwasaki; Masahiro Murakami; Yoshinobu Ijiri; Muneshige Shimizu; Junichiro Yamamoto (Future Science OA)
Aim: Epidemiologic studies support the assumption (French paradox hypothesis) that drinking red wine is beneficial in the prevention of cardiovascular diseases. Our recent works however cast doubt on such claim. Earlier we have shown that the antithrombotic activity of various fruits and vegetables mainly depends on their varieties. For this reason, several varieties of red and white grapes were tested for antithrombotic effect in animal experiments. Results: Antithrombotic effect of 45 red and white grape varieties were assessed in the present study. Out of the 45, one red grape variety showed antithrombotic effect, while the majority of red and white grape varieties enhanced thrombosis. Conclusion: Most red and white grape varieties enhanced thrombotic activity of blood.